Punicic acid ameliorates obesity and liver steatosis by regulating gut microbiota composition in mice - Yuan, Gaofeng; Tan, Meijuan; Chen, Xiaoe (Food & function, 2021)
This study aimed to elucidate the effect of punicic acid (PUA, cis 9, trans 11, cis 13-18 : 3) on obesity and liver steatosis in mice induced by high-fat diet (HFD), and to explore the possible mechanism. Mice were fed with either a HFD or a control diet for 8 weeks. Half of HFD-mice received daily supplementation of PUA. Supplementation with PUA ameliorated the liver steatosis and obesity in mice fed by HFD, as demonstrated by the decreased hepatic triglyceride accumulation, body weight gain and fat weight. A HFD increased the ratio of Firmicutes to Bacteroidetes , whereas supplementation with PUA effectively restored it. PUA supplementation counteracted the upregulation in family Desulfovibrionaceae and Helicobacteraceae , and the downregulation in Muribaculaceae and Bacteroidaceae induced by HFD. Correspondingly, the family of Desulfovibrionaceae was positively related, whereas Muribaculaceae was negatively related to the amount of epididymal and perirenal fat, and the level of liver triglyceride and total cholesterol. The family Helicobacteraceae was also positively related to the amount of epididymal and perirenal fat. Moreover, PUA supplementation counteracted the increase in the population of Anaerotruncus , Faecalibaculim , Mucispirillum , and the decrease in the population of Lactobacillus , Roseburia , Oscillibacter at the genus level induced by HFD. These results demonstrated that PUA can at least in part ameliorate obesity and liver steatosis in mice induced by HFD by regulating gut microbiota composition. PUA could ameliorate obesity and liver steatosis in mice induced by HFD via regulating the gut microbiota composition.